2020
DOI: 10.1016/j.molmet.2020.101056
|View full text |Cite
|
Sign up to set email alerts
|

Lactate activation of α-cell KATP channels inhibits glucagon secretion by hyperpolarizing the membrane potential and reducing Ca2+ entry

Abstract: Objective Elevations in pancreatic α-cell intracellular Ca 2+ ([Ca 2+ ] i ) lead to glucagon (GCG) secretion. Although glucose inhibits GCG secretion, how lactate and pyruvate control α-cell Ca 2+ handling is unknown. Lactate enters cells through monocarboxylate transporters (MCTs) and is also produced during glycolysis by lactate dehydrogenase A (LDHA), an enzyme expressed in α-cells. As la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 84 publications
4
22
0
Order By: Relevance
“…In addition to glycolysis, LDH activity was found to be present in the K ATP microcompartment and efficiently drive NAD + production to support glycolysis at the GAPDH step in both human α and β cell membranes. In support of previously published work 32,3537 , we found that lactate opens K ATP channels and opposes PK-mediated K ATP closures in mouse α cells. Since lactate can reach millimolar levels in the blood, and α-cells express a high level of MCT pyruvate/lactate transporters ( Slc16a1 ) 32 , lactate regulation of K ATP channels is expected to occur in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to glycolysis, LDH activity was found to be present in the K ATP microcompartment and efficiently drive NAD + production to support glycolysis at the GAPDH step in both human α and β cell membranes. In support of previously published work 32,3537 , we found that lactate opens K ATP channels and opposes PK-mediated K ATP closures in mouse α cells. Since lactate can reach millimolar levels in the blood, and α-cells express a high level of MCT pyruvate/lactate transporters ( Slc16a1 ) 32 , lactate regulation of K ATP channels is expected to occur in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to glycolysis, LDH activity was found to be present in the K ATP micro-compartment by driving its NAD + production to support glycolysis at the GAPDH step in both human α and β cells. In support of previously published work 27,3032 , we found that lactate opens K ATP channels and opposes PK-mediated K ATP closures in mouse α cells, which express a high level of MCT1 ( Slc16a1 ) 27 . However, lactate derived from glycolytic pyruvate had no impact on K ATP channels in our experiments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pathway enrichment analysis shows that LDHB and PKM participate in glucagon signaling pathway, connected with nutrient deprivation and the breakdown of cell glycogen. Interestingly, the substrate of LDHB, lactate, and the product of PKM, pyruvate, reduce the secretion of glucagon in pancreatic cells, 54 while glucagon deactivates the PKM enzyme, inhibiting glycolysis and regulating glucose homeostasis 55 . Therefore, the up‐regulation of these two glycolytic enzymes, may reflect the impairment of glucose/glycogen metabolism in PD 56 …”
Section: Discussionmentioning
confidence: 99%
“…Widefield or confocal microscopy was used to measure βand δ-cell intracellular Ca 2+ ([Ca 2+ ] i ) and cAMP levels using fluorescent dyes or genetically encoded indicators as previously described. 33,34 A detailed description can be found in Appendix S1.…”
Section: Intracellular Ca 2+ and Camp Recordingsmentioning
confidence: 99%